Pengaruh Kompetensi, Pengalaman Kerja, dan Integritas Terhadap Kualitas Hasil Audit Aparat Pengawas Internal Pemerintah Provinsi Sulawesi Selatan - Irhan Kamal; Murdifin Haming; Fadliah Nasaruddin (STIE AMKOP, 2019)
The purpose of this research is to test and analyze the influence of competency, working experience, and integrity to the quality of audit result of internal auditor in South Sulawesi Province. This research uses a quantitative approach by using primary data through a survey of 63 people as a sample from the internal auditor of the South Sulawesi Province as population. The method of data analysis uses statistical analysis and multiple linear regression using the SPSS Program. The result shows that competency, working experience, and integrity have significant effect on the Quality of Audit Results of the internal auditor apparatus of South Sulawesi Province. The direction of positive relationship indicates that the increasing competence, working experience, and integrity improves the quality of the audit result of the internal auditor apparatus of South Sulawesi Province. Keywords: Competency, Working Experience, Integrity, and Quality of Audit Result of Internal Auditor Apparatus of the Government